Developmental origin of limb size variation in lizards. Issue 3 (May 2017) - Andrews, Robin M.; Skewes, Sable A.
Abstract : In many respects, reptile hatchlings are fully functional, albeit miniature, adults. This means that the adult morphology must emerge during embryonic development. This insight emphasizes the connection between the mechanisms that generate phenotypic variation during embryonic development and the action of selection on post‐hatching individuals. To determine when species‐specific differences in limb and tail lengths emerge during embryonic development, we compared allometric patterns of early limb growth of four distantly related species of lizards. The major questions addressed were whether early embryonic limb and tail growth is characterized by the gradual (continuous allometry) or by the abrupt emergence (transpositional allometry) of size differences among species. Our observations supported transpositional allometry of both limbs and tails. Species‐specific differences in limb and tail length were exhibited when limb and tail buds first protruded from the body wall. Genes known to be associated with early limb development of tetrapods are obvious targets for studies on the genetic mechanisms that determine interspecific differences in relative limb length. Broadly comparative studies of gene regulation would facilitate understanding of the mechanisms underlying adaptive variation in limb size, including limb reduction and loss, of squamate reptiles.